INVESTIGATING THE UNDERSTANDING, USE AND EXPERIENCES OF OLDER PEOPLE IN LINCOLNSHIRE ACCESSING EMERGENCY AND URGENT SERVICES VIA 999 AND NHS 111: A SCOPING STUDY. Issue 5 (18th April 2015) - Togher, Fiona; Windle, Karen; Essam, Nadya; Hardwick, Jialin; Phung, Viet-Hai; Vowles, Valerie
Abstract : Introduction: During 2011/12, East Midlands Ambulance Service (EMAS) received 776, 000 emergency 999 calls of which 36% (277, 000) did not require transportation to hospital. Inappropriate calls can be due to public misunderstanding of when it is appropriate to ring 999. NHS 111 is an alternative free telephone service that enables the public to access health care advice or resources when the matter is urgent but not a 999 emergency. However knowing which service to telephone is not always easy and such a decision can be particularly difficult for older people as symptom presentation across complex co-morbidities can be atypical. A mixed method scoping project was carried out to explore the understanding, use and experiences of emergency (999) and urgent services (NHS 111) by older people aged 65 and over. Here, we report findings from the qualitative workstream. Methods: Semi-structured interviews and focus groups (n=25) using a topic guide were carried out with a purposive sample of older people who had used the 999 ambulance service and/or the NHS 111 service in the East Midlands. Results: We found a lack of awareness as to the remit of NHS 111 and confusion as to when this number should be phoned. Older people's expectations of 111 seemed to be analogous to other primary care services. As a consequence, participants were often dissatisfied with the service response; it neither provided useful advice nor reassurance. Greater satisfaction was reported with the call handling process and hospital transportation through EMAS (999) and older people's reported rationale for phoning 999 would seem to suggest appropriate service use. Conclusion: Developing a greater understanding of how older people decide to contact a service would support future policy and practice implementation. If the remit of a service is unclear and accompanying publicity confusing, older people will continue to dial 999.